Drug Delivery: Surfactant‐Stripped Cabazitaxel Micelles Stabilized by Clotrimazole or Mifepristone (Adv. Therap. 3/2020). Issue 3 (12th March 2020) - Sun, Boyang; Chitgupi, Upendra; Li, Changning; Federizon, Jasmin; Zhang, Changjie; Ruszaj, Donna M.; Razi, Aida; Ortega, Joaquin; Neelamegham, Sriram; Zhang, Yumiao; Lovell, Jonathan F
Abstract : The cover image representing article number 1900161 by Jonathan F Lovell and co‐workers shows aggregates formed by the anti‐cancer drug cabazitaxel. In this work, it is shown that by co‐formulating cabazitaxel in unique surfactant micelles with certain other hydrophobic cargo, aggregation can be prevented, resulting in a potent chemotherapy formulation with long‐term liquid storage stability and a high drug‐to‐excipient ratio.